Visual metaphors in photography the role of hard-sell visual in conveying a message / Ahmad Sofiyuddin Mohd Shuib - Mohd Shuib, Ahmad Sofiyuddin (UiTM Perak Press, 2021)
Social distance is one of the Standard Operation Procedures (SOP) that has been set by WHO (World Health Organization) and also the Malaysian government to break the chain of Coronavirus disease (COVID-19) since this pandemic is widespread in every country. Various message and visual mediums were issued to warn the public about the importance of social imprisonment, but there are still some people who do not heed the instructions of this SOP by not practicing social imprisonment with each other. To convey the message in an alternative and creative way, visual metaphor is chosen to attract the attention of the audience to understand the message presenter. Visual metaphor representing a idea, concept, person, place, or thing through an image that uses an analogy or association. The selection of visual metaphors is selected based on its uniqueness in visual communication where dimensions for hard sell appeal are thinking, explicitness and fact (Peltoniemi, 2015). The choice of the subject of these oyster mushrooms shall be chosen on the basis of the natural conditions of those growing on the trunks of the leaves in groups and distances. This way of growing distance inspires one to use it as a message to the audience through Visual Metaphor. With the use of this visual metaphor, it can educate the audience to deepen the message and the work.